An Examination of the Qir???t Attributed to Zayd ibn Th?bit - Saylan, Nesrişah (Diyanet İşleri Başkanlığı, 2026)
This study examines the qir???t variants attributed to Zayd b. Th?bit, a figure widely recognized for scholarly authority in the field of qir???t, through an analysis of both qir???t and tafs?r literature. Its aim is to clarify Zayd b. Th?bit’s position within the science of qir???t and to assess his contributions to the interpretation of Qur??nic verses. Several factors attest to his authority in this discipline: he is reported to have received his recitation directly from the Prophet Mu?ammad; leading Companions, most notably Ibn ?Abb?s, are said to have based their own recitational preferences on his reading; and the chains of transmission of most of the Im?ms of the ten canonical readings include Zayd b. Th?bit. The primary objective of the research is to identify the qir??a variants ascribed to Zayd b. Th?bit, analyze their interpretive implications, and evaluate them within the broader relationship between qir???t and tafs?r. To this end, relevant qir???t and tafs?r sources are surveyed, and the variants attributed to Zayd b. Th?bit are systematically classified. The study’s distinctive contribution lies in its demonstration of Zayd b. Th?bit’s authority in qir???t through close, meaning-oriented analyses of the variants associated with his recitation. While previous scholarship has addressed his role in the Qur??nic sciences more generally, the direct examination of his qir??a variants in relation to specific verses, and the articulation of their impact on verse interpretation, set this study apart. In doing so, it offers a framework for understanding the qir??a tradition in the era of the Companions and illuminates the close interrelationship between qir???t and the science of tafs?r.

Bu çalışma, kıraat alanında otorite kabul edilen Zeyd b. Sâbit’e nispet edilen okuyuş vecihlerini, kıraat ve tefsir literatürü çerçevesinde inceleyerek onun kıraat ilmindeki konumunu ve Kur’an âyetlerinin anlaşılmasına sunduğu katkıları ortaya koymayı amaçlamaktadır. Zeyd b. Sâbit’in kıraatini doğrudan Hz. Peygamber’den (s.a.s.) almış olması, İbn Abbâs gibi önde gelen isimlerin kıraat tercihinde genellikle onun okuyuşunu esas alması, kıraat-i aşere imamlarının çoğunun isnadında yer alması onun bu alandaki yetkinliğinin göstergeleri arasında yer almaktadır. Araştırmanın temel hedefi, Zeyd b. Sâbit’e nispet edilen kıraat vecihlerini tespit etmek, bu vecihlerin âyetlerin anlaşılmasına olan katkılarını incelemek ve kıraattefsir ilişkisi bağlamında değerlendirmektir. Bu doğrultuda kıraat ve tefsir kaynakları taranmış, Zeyd b. Sâbit’e atfedilen kıraat örnekleri sistematik olarak sınıflandırılmıştır. Çalışmanın özgün yönü, Zeyd b. Sâbit’in kıraat ilmindeki otoritesini, ona nispet edilen kıraat vecihlerinin anlam merkezli ortaya koymasıdır. Mevcut literatürde Zeyd b. Sâbit’in Kur’an ilimlerindeki rolü ele alınmış olmakla birlikte, onun kıraat vecihlerinin doğrudan âyetlerle ilişkilendirilerek incelenmesi ve bu okuyuşların âyetin anlaşılmasına olan katkılarının ortaya konulması, bu çalışmayı önceki araştırmalardan ayırmaktadır. Bu yönüyle araştırma, yalnızca sahabe dönemindeki kıraat geleneğine dair bir çerçeve sunmakla kalmamakta; aynı zamanda kıraat ile tefsir ilmi arasındaki ilişkiyi de ortaya koymaktadır.
Zeyd b. Sâbit’e Atfedilen Kıraat Rivâyetlerinin Değerlendirilmesi
Keywords: Recitation of the Qur'an and Qiraat; Kuran-ı Kerim Okuma ve Kıraat